Influence of the Multicavity Shape on the Solid Scramjet - Pengnian Yang; Zhixun Xia; Likun Ma; BinBin Chen; Yunchao Feng; Chaolong Li; Libei Zhao (International Journal of Aerospace Engineering)
In this paper, a modular solid scramjet combustor with multicavity was proposed. The influence of multicavity shape on the performance of solid scramjet was investigated by the direct-connected tests. The experiments simulated a flight Mach 5.5 at 25 km. The boron-based fuel-rich propellant was used. The microstructure of combustion products was analyzed by SEM. The experimental results show that the fuel-rich mixture produced by the gas generator would ignite rapidly in the solid scramjet combustor. The combustion process showed a typical characteristic of establishment-development-maintenance-attenuation. Compared to the flame-holding cavity, the other shapes of cavities, e.g., narrow and lobe, can improve mixing and combustion. In our experiment, the combustion efficiency increased from 0.41 to 0.48, and the total pressure recovery was 0.36. In summary, the proposed solid scramjet combustor can effectively solve the ignition delay problem of the fuel-rich mixture, and the narrow/lobe cavity shows the ability to improve the mixing and combustion of the fuel-rich mixture.